Book Do Not Kill, the Readers Do So: Reflections on the Violence-Breeding Employment of Christianity - Najib George Awad (Journal of Religion and Decoloniality, 2025)
This essay offers an overview of the phenomenon of violence in today’s public squares from a Christian perspective. It tries to anatomize the link that connects religiosity with violence and whether the latter is the by-product of the former at every case or not. It demonstrates that studying violence from a Christian perspective avoids approaching the religion-violence relation from either ‘all organized violence is religiously inspired’ or ‘religion is entirely benevolent’ one-sided position. The essay, then, proposes that there are considerably factual situations of secularly, politically, culturally and socially rooted violence that generates its own version of religious explanation and manifestation to implement in the service of its legitimization and longevity and for the sake of endowing its existence with necessity and significance.